Utilization of the Maze Chase Wordwall Online Gamification Feature as a Digital Learning Medium for Statistics and Probability Subject - Yuyun Khairunisa (2021)
Gamification is a processÂ of combining in-game rules, namely patterns, design, and game mechanics that aim to changing non-game activities into learningÂ activities to make them more attractive to users. That is whatÂ we want to prove in this research because games are believed toÂ provide various benefits from the psychological aspects of user bothÂ cognitively, emotionally, and socially, so that they can increase theÂ interest and interactivity of students. The method used is descriptive quantitative. There are several online gamification platforms that are widely used, one of which is â€œwordwallâ€. The author makes useÂ of one of the online features on the platform and then evaluatesÂ learning outcomes. The result of the study shows that the value asÂ a benchmark for learning outcomes obtained by students after theÂ application of the gamification feature is greater than before the online gamification feature was implemented.